The Herd of Winners: Authoritarian Narcissism as a Neoliberal Government Device (Andamios, Revista de Investigación Social, 2025)
Being a winner in the neoliberal society is no longer a result of economic competition, but a disposition towards competition itself. Following this interpretative key, the article studies authoritarian narcissism as the mode of autoeroticization that, in convergence with the governmental strategies of neoliberal governmentality, divides society into two existential communities: winners and losers. The identification of a theological-sporting matrix in neoliberal governmentality leads us to conclude, in convergence with José Luis Villacañas Berlanga and against Byung-Chul Han’s thesis, that neoliberal power cannot be explained without understanding its theological offer.
Keywords: Narcissism; authoritarianism; competition; theology; neoliberalism